New technology of magnetohydrodynamic purification of water and information-measuring system for its control - Shabatura, Yu. V.; Hrytsiuk, A. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper introduces the physical principles of magnetohydrodynamic system operation for water purification. On the basis of the experimental research a new method for optimal operation of the magnetohydrodynamic system using integrated information-measuring system to control output voltage and input water steam is proposed.